THE WATER-UNDERSATURATED AND DRY QZ-AB-OR SYSTEM REVISITED. EXPERIMENTAL RESULTS AT VERY LOW WATER ACTIVITIES AND GEOLOGICAL IMPLICATIONS - Holtz F.; Becker A.; Freise M.; Johannes W. (My University, 2001)
Liquidus phase relations have been determined in the system Qz-Ab-Or-H2O at H2O-undersaturated conditions (melt water content of 1 wt% H2O) in the pressure range 200-800 MPa. Starting materials were homogeneous synthetic glasses containing 1 wt% H2O. The minimum liquidus temperatures of the ternary system Qz-Ab-Or are 925 +/- 15 degreesC at 200 MPa, 990 +/- 10 degreesC at 500 MPa, and 1,050 +/- 10 degreesC at 800 MPa. The normative Qz content of the minimum is 34 +/- 2% at 200 MPa (the exact Ab/Or ratio could not be determined). The composition of the minimum is QZ(32)Ab(35)Or(33) at 500 MPa, and Qz(29)Ab(37)Or(34) at 800 MPa (Qz/Ab/Or expressed as normative proportions). At a given pressure, the Qz content of the minimum composition in the system Qz-Ab-Or-H2O remains constant with changing a(H2O) The Qz content of the minimum composition increases with decreasing pressure and the normative Ab/Or ratio remains approximately constant (for a water content of the melt of 1 wt%). The determined liquidus temperatures in eutectic or minimum melts with 1 wt% H2O, and the effect of pressure on the liquidus temperature are higher than estimated previously (ca. +0.2 degreesC:MPa between 200 and 800 MPa instead of less than +0.1 degreesC/MPa in previous estimations). Thus, at a given pressure, temperature and water content, the melt productivity in quartzofeldspathic rocks (such as metagreywackes) is lower than predicted from previous models. The experimental results show (1) that adiabatic decompression in the quartz-alkali feldspar system containing 0-3 wt% H2O produces more melt than expected. which is of importance for the evolution of ascending dacitic and rhyolitic magmas, and (2) that previously published dry liquidus temperatures are strongly underestimated at high pressure (approximately 75 degreesC at 500 MPa).